2012
DOI: 10.1590/s0004-28032012000100008
|View full text |Cite
|
Sign up to set email alerts
|

Common bile duct stones: analysis of the videolaparoscopic surgical treatment

Abstract: -Context -About 9% of the Brazilian population has gallstones and the incidence increases significantly with aging. The choledocholithiasis is found around 15% of these patients, and a third to half of these cases presented as asymptomatic. Once the lithiasis in the common bile duct is characterized through intraoperative cholangiography, the laparoscopic surgical exploration can be done through the transcystic way or directly through choledochotomy. Objective -To evaluate the results and outcomes of the lapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
0
7
0
5
Order By: Relevance
“…None of the 25 studies reported mean BMI. Only one study 20 reported the preoperative laboratory investigation (median (range) bilirubin concentration for LTCE 20 (6-74) μmol/l and Reference Gigot et al 31 Millat et al 34 Arvidsson et al 20 Martin et al 33 Lauter and Froines 24 Tokumura et al 40 Waage et al 42 Jameel et al 22 Zhang et al 19 Hongjun et al 18 Aawsaj et al 28 Overall Heterogeneity: 31 Arvidsson et al 20 Martin et al 33 Lauter and Froines 24 Tokumura et al 40 Waage et al 42 Zhang et al 19 Overall Phillips et al 36 Millat et al 34 Berthou et al 29 Michel et al 25 Topal et al 41 Tan et al 39 Santo et al 38 Mohamed et al 35 Rhodes et al 37 Cuschieri et al 30 Phillips et al 36 Gigot et al 31 Millat et al 34 Berthou et al 29 Martin et al 33 Tokumura et al 40 Waage et al 42 Jameel et al 22 Tai et al 23 Tan et al 39 Zhang et al 19 Aawsaj et al 28 Overall Hongjun et al 18 Berthou et al 29 Martin et al 33 Overall Hongjun et al 18 Reference...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the 25 studies reported mean BMI. Only one study 20 reported the preoperative laboratory investigation (median (range) bilirubin concentration for LTCE 20 (6-74) μmol/l and Reference Gigot et al 31 Millat et al 34 Arvidsson et al 20 Martin et al 33 Lauter and Froines 24 Tokumura et al 40 Waage et al 42 Jameel et al 22 Zhang et al 19 Hongjun et al 18 Aawsaj et al 28 Overall Heterogeneity: 31 Arvidsson et al 20 Martin et al 33 Lauter and Froines 24 Tokumura et al 40 Waage et al 42 Zhang et al 19 Overall Phillips et al 36 Millat et al 34 Berthou et al 29 Michel et al 25 Topal et al 41 Tan et al 39 Santo et al 38 Mohamed et al 35 Rhodes et al 37 Cuschieri et al 30 Phillips et al 36 Gigot et al 31 Millat et al 34 Berthou et al 29 Martin et al 33 Tokumura et al 40 Waage et al 42 Jameel et al 22 Tai et al 23 Tan et al 39 Zhang et al 19 Aawsaj et al 28 Overall Hongjun et al 18 Berthou et al 29 Martin et al 33 Overall Hongjun et al 18 Reference...…”
Section: Resultsmentioning
confidence: 99%
“…The median quality score for the RCTs was judged based on the Cochrane Handbook 13 . The quality assessment stratifies the current evidence and projects the need for further research on the topic based on the quality of the available evidence into: high-quality evidence where further research is not expected to change the current confidence in the estimate of the effect size, moderate-quality evidence if further research is likely to influence confidence in the estimated effect and may change it; low-quality evidence if further research is very likely to influence confidence in the estimate of Reference Design n-RCT Phillips et al 36 Gigot et al 31 Millat et al 34 Arvidsson et al 20 Berthou et al 29 DePaula et al 27 Martin et al 33 Lauter and Froines 24 Michel et al 25 Tokumura et al 40 Waage et al 42 Topal et al 41 Jameel et al 22 Tan et al 39 Santo et al 38 Dimov et al 26 Darrien et al 21 Mohamed et al 35 Zhang et al 19 Aawsaj et al 28 Rhodes et al 37 Cuschieri et al 30 Grubnik et al 32 Overall n-RCT heterogeneity: I 2 = 68%, P < 0·05 RCT heterogeneity: I 2 = 72% P < 0·05 Heterogeneity: 2 Forest plot for successful duct clearance in patients with choledocholithiasis undergoing a laparoscopic transcystic or transcholedochal approach. Studies that had 100 per cent success in both arms 18,23 were not included in the analysis, so calculation of an odds ratio was not possible in the pooled analysis.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Endoscopic Retrograde Cholangiopancreatography (ERCP), which was introduced into the field of gastroenterology, hepatology and hepato-pancreatico-biliary surgery, has progressed to be an important and essential diagnostic and therapeutic tool for biliary and pancreatic diseases but haemorrhagic complications usually occurs when utilizing Endoscopic Sphincterotomy (EST) or Endoscopic Papillotomy (EPT) [1][2][3][4]. The complication of subcapsular hepatic hematoma after conducting ERCP is uncommon and a likely life-threatening situation in which few cases was reported in the world [5].…”
Section: Introductionmentioning
confidence: 99%
“…З розвитком ендовідеохірургічної апаратури та інструментарію, накопиченням досвіду і вдо-сконаленням хірургічної техніки все ширше за-стосовується одноетапна тактика лікування, що включає втручання на жовчній протоці, літоек-стракцію і холецистектомію лапароскопічним способом [10, 11, 12,13,14,15, 16].…”
unclassified